(untitled) (CIPEEX, 2025)
Nanotechnology has emerged as one of the most innovative areas of science, especially in the fields of health and aesthetics. Its potential lies in its ability to manipulate particles at the nanoscale, enabling direct interactions with cells and fundamental biological mechanisms. In aesthetics, this technology enables the development of minimally invasive procedures that combine efficacy and greater patient safety. The aim of this study is to analyze the role of nanoparticles in aesthetic health, highlighting their mechanisms of cellular action, clinical applications, benefits, and associated risks. A narrative review of scientific literature was conducted, considering publications from recent years that addressed the use of nanoparticles in aesthetic and therapeutic procedures. The main descriptors used were: nanotechnology, nanoparticles, drug delivery, and biosafety. It was observed that nanoparticles have the ability to cross cell membranes and accumulate in specific organelles, favoring the targeted delivery of bioactive substances. This property has been applied in procedures such as drug delivery associated with microneedling, carboxytherapy, and the use of biostimulants. These strategies allow for the controlled release of rejuvenating, moisturizing, and depigmenting active ingredients, enhancing clinical effects and reducing tissue aggression. However, studies also indicate concerns related to toxicity, the risk of tissue accumulation, and the need for stricter regulations to ensure patient safety. The conclusion is that the incorporation of nanotechnology into aesthetic care represents a promising advance, with the potential to make procedures more effective and less invasive. However, its use must be accompanied by specific regulations and ongoing biosafety research, ensuring that clinical benefits are always aligned with the individual’s protection and well-being.